Evaluation of the implementation of the ACEP cycle and learning motivation on students’ exposition writing ability - Hidayat, Ryan; Lapasau, Merry; Andayani, Andayani; Anindyarini, Atikah (BAHASTRA, 2025)
The ACEP cycle is a modified form of the APOS learning theory, which is designed as a pedagogical strategy consisting of four main elements: (A) Activities, (C) Class discussion, (E) Exercises, and (P) Performance. This cycle modification is applied to improve students' writing skills, especially their writing skills. The main focus of this study is to evaluate the effectiveness of the ACEP cycle in improving students' expository writing skills, as well as to analyze the relationship between the application of the ACEP cycle and learning motivation towards improving these writing skills. The ACEP cycle implemented in two junior high schools in Bogor Regency was evaluated using a mix-method method. The research sample was taken from the total population using a random (probabilistic) sampling approach. The research tools (questionnaires, interviews, and writing assessments) have been previously validated. The results of this study can be seen from the results of ANOVA with a sig value = 0.036 and Fh = 4.639, so H0 is rejected and H1 is accepted. This means that there is a significant interaction effect of the ACEP cycle and learning motivation on students' exposition writing skills.